Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Komitmen Organisasi Dan Terhadap Kinerja Pegawai Unit Pelaksana Teknis Pengujian Dan Pengembangan Pakan Ternak Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara - Muliani, Sri; Fahmi, Nur Augus (Manajemen dan Bisnis, 2024)
The formulation in this study are: How the influence of work discipline and job satisfaction on organizational commitment and its impact on employee performance. This study aims to determine the effect of work discipline and job satisfaction on organizational commitment and its impact on employee performance. With non-probability sampling techniques, the samples in this study were 32 people. The results showed; Work discipline has a direct effect on organizational commitment; Job satisfaction has a direct effect on organizational commitment; Organizational commitment has a direct effect on employee performance; Job satisfaction has a positive and significant impact on employee performance through organizational commitment; Job satisfaction has a positive and significant impact on employee performance through organizational commitment; Work discipline and job satisfaction simultaneously have a positive and significant effect on organizational commitment and impact on employee performance